How toddlers new to child care become members of a classroom community. Issue 3 (17th February 2022) - Eun McDevitt, Seung; Recchia, Susan L.
ABSTRACT: Transitioning into child care can bring complex emotional tensions and have a lasting and powerful impact on future separations and caregiving encounters. Despite the increasing number of children in child care programmes and the complexity surrounding the phenomenon, little attention has been given to especially very young children's entry into child care settings and their daily transitional experiences. Using a phenomenological multi-case study approach, we aimed to capture children's daily experiences from their perspectives, by looking closely at their behaviours, movements, and talk, supplemented by parents' and teachers' perceptions and reflections on the children's experiences. Our data illuminate the diverse ways a group of toddlers new to childcare navigated the process of becoming members of the classroom community, the differences in their subtle and overt emotional tensions, verbal and non-verbal communication styles, and evolving identity and agency. Teachers' roles unfolded in response to children's diverse needs and ways of being.